PENINGKATAN KUALITAS LAYANAN INTERNET SEKOLAH DENGAN METODE POLICY BASED ROUTE (PBR) DI SMK PP NEGERI 1 TEGALAMPEL BONDOWOSO - Lalitya Nindita Sahenda; Prayugo Ardi Wibowo; Pramuditha Shinta Dewi Puspitasari (Gapenas Publisher, 2024)
Nowadays, internet connectivity is very important in various aspects. All sectors of life require an internet connection, for example in the communications, economic, social and educational sectors. The massive development of internet connections has had a positive impact on various sectors. including the education sector. Before the massive development of the internet, education in schools was carried out manually, for example the teacher would explain on the blackboard. But with the development of the internet, learning media is built by utilizing the internet. Students can also easily find the learning materials they need on the internet. Not only teachers and students, other entities in the school, namely administrative staff, also need a reliable internet network to make it easier to report school activities, for example attendance, finances, personnel, etc. All of these activities require a reliable and fast internet connection at school. Unfortunately, for partners, the internet is still slow and often disconnects, so it is necessary to add a new internet service provider (ISP) to support the previous ISP. Apart from that, it is also necessary to rejuvenate internet devices, as well as network management so that the 2 connected ISPs can be used optimally and optimally. Network management is by implementing the Policy Based Route (PBR) method. This method allows the load to be adjusted to be balanced across the 2 ISPs used. So as to avoid overload/overload on the school network. The availability of reliable and fast internet is an effort to improve the quality of school internet services which can support teaching and learning activities optimally